(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
The paper aims at analysing the most relevant examples of the use of artificial intelligence within the Italian public administrations, in order to highlight related benefits and risks. It focuses on the internal organization, rulemaking and enforcement decisions. There appears to be a need for a general regulatory framework, as well as for specific procedural disciplines in each administration in order to allow real accessibility, comprehensibility and non-discrimination for the stakeholders. At the same time, these disciplines should introduce mechanisms and evaluation adequate to verify the appropriateness of the use of artificial intelligence instead of human intelligence, with a view to the effectiveness of organization and administrative action.